Organização do trabalho escolar no processo de implementação da BNCC e do Referencial Curricular Gaúcho: limites e possibilidades - Matos, Eder Henriques de (2021)
This research aimed to study the process of construction of pedagogical proposals by the collective of teachers in the context of curriculum restructuring of the final years of elementary and high school of a State School of Basic Education. More specifically, we sought to answer the following research problem: what possibilities and limits are perceived in the process of implementation of the National Common Curricular Base (BNCC) and the Curricular Reference Gaucho (RCG) in the final years of elementary school and high school in a State School of Basic Education located in the west of Santa Maria RS? Therefore, the qualitative methodology was chosen as an approach for this research, because through it it is possible to analyze the school routine, considering the perceptions of those involved. To collect information, observations were made of the pedagogical formations carried out at school in 2019, through records in the form of field notes prepared by the researcher, and focus groups were carried out with a part of the teachers of the final years and high school, which were performed virtually, due to the Covid-19 pandemic, in 2020. Among the teachers' narratives, it is possible to perceive their discomfort and discontent in receiving ready-made documents, which do not account for the singularities of each school context. The very formations that intend to implement changes in the educational system are already organized and planned by someone who does not know the context of each school, which corroborates that such changes occur in a fragile way, because they are little discussed with the main involved, those who are at the tip of the process and who will be responsible for putting into practice these new educational guidelines , i.e. teachers. Tied to this, considering the context of the pandemic, it was observed the exhaustion of education professionals in the face of the challenges of hybrid education instituted during the pandemic. It was evidenced that, although school autonomy has been requested and proclaimed for a long time, it is still flagged as a fragile issue, where teachers question the lack of freedom to work in schools, showing that the issue of democratic management and school autonomy do not yet occur effectively. It is concluded that it is necessary to consider the importance of curricular changes and the strengthening of a common national base, because they are important and necessary processes for public education to reinvent itself and stop being seen as a failure. However, for these to occur, it is essential an educational political organization focused on the real pedagogical, social and structural needs of teachers, students and management, considering their particularities. As well as, to understand the relevance of thinking about the school from within itself, according to its reality, bringing to the participation the main involved in this process, that is, the school community, students and especially teachers.